Originally Posted by

**ArTiCK** Hi all,

Using the s shifting theorem to find the inverse Laplace transform of:

F (s) = 3 / (s + 2)^2

I get the right answer but i am not sure if my working out is correct, would be appreciated if someone can tell me.

F(s +2) = L [e^(2t)* f(t)]

L[f(t)] = 3/ s^2

f(t) = L^(-1) [3/ s^2]

= 3t

g(t) = e^(2t) * f(t) Mr F says: This should be $\displaystyle {\color{red}e^{-2t} \cdot f(t)} $. Note that F(s + 2) = F(s - [-2]) ....

g(t) = 3t*e^(2t) Mr F says: This should be $\displaystyle {\color{red}3t \cdot e^{-2t}} $

Thanks in advance,

ArTiCk